2021
DOI: 10.1007/s11249-021-01438-6
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Steel Composition on the Formation and Effectiveness of Anti-wear Films in Tribological Contacts

Abstract: The effectiveness of antiwear additives in laboratory tests is commonly evaluated using specimens made of AISI 52100 through-hardened bearing steel. However, many lubricated machine components are made of steels with significantly different material compositions, which raises an important practical question of whether the performance of antiwear additives with these other steel types is different from that established with AISI 52100. To help answer this question, this paper investigates the influence of steel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…Interestingly, up to the 3 m/s test stage, DDP and TPP formed relatively thin tribofilms of less than 10 nm, but their film thicknesses then grew to more than 20 nm above this sliding speed stage. It has been shown that these ashless P-S additives form films more slowly that ZDDPs [32]. MoDTC formed a thick tribofilm of around 10 nm to 15 nm quite early in the test sequence and this remained stable up to 6 m/s.…”
Section: Scuffing Behaviour At 20 Nmentioning
confidence: 99%
“…Interestingly, up to the 3 m/s test stage, DDP and TPP formed relatively thin tribofilms of less than 10 nm, but their film thicknesses then grew to more than 20 nm above this sliding speed stage. It has been shown that these ashless P-S additives form films more slowly that ZDDPs [32]. MoDTC formed a thick tribofilm of around 10 nm to 15 nm quite early in the test sequence and this remained stable up to 6 m/s.…”
Section: Scuffing Behaviour At 20 Nmentioning
confidence: 99%
“…5,6,11 Thus, recent studies have focused on the influence of metallic and nonmetallic substrates in the tribochemical reactions of MoDTC [12][13][14] and ZDDP. [15][16][17] Chlorine-containing EP additives are commonly used in the cold-working processes of steel because of their cost effectiveness and high lubricity along with high corrosion resistance. 3 However, their application is limited owing to environmental and public health hazards such as carcinogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, MoDTC reduces friction by forming a MoS 2 tribofilm on the contact area, 7–10 whereas ZDDP prevents wear by forming an amorphous tribofilm with multilayered structures 5,6,11 . Thus, recent studies have focused on the influence of metallic and nonmetallic substrates in the tribochemical reactions of MoDTC 12–14 and ZDDP 15–17 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was recently reported that the tribofilm formation kinematics could be affected by the steel composition depending on the lubrication additives. Pagkalis et al found that the boundary lubrication effectiveness of ashless anti-wear additives on 100Cr6, M2, 16MnCr5 and 440C steels was significantly different, while the ZDDP tribofilm was little influenced by the steel composition (Pagkalis et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In tribological contacts, surface films are sometimes generated on the worn surface that significantly influence the tribological behaviors of steels and other metals. Typical examples include tribofilms generated by oil additives on surfaces of engine steels (Gellman and Spencer, 2002;Spikes, 2004) and oxide film spontaneously formed on surfaces of passive metals (Feyzi et al, 2022;Sun and Bailey, 2023;Toh et al, 2018). However, depending on their nature, the generated surface films affect the friction and wear behaviors of metals in various manners (Cao et al, 2016;Carrington et al, 2021;Luiz and Spikes, 2020;Mittal et al, 2022;Topolovec-Miklozic et al, 2008).…”
Section: Introductionmentioning
confidence: 99%